Measuring instructors continued intention to reuse Google Classroom in Iraq: a mixed-method study during COVID-19 - Hussein M.H.; Ow S.H.; Ibrahim I.; Mahmoud M.A. (Emerald Group Holdings Ltd., 2023)
Purpose: The use of learning management systems (LMSs) such as Google Classroom has increased significantly in higher education institutes during the COVID-19 pandemic. However, only a few studies have investigated instructors continued intention to reuse LMS. The purpose of this study is to investigate the factors that influence instructors intention to reuse an LMS in higher education institutes. Design/methodology/approach: This study adopted a mixed-method research design. In the quantitative section, an integrated model of technology acceptance model and information system success model is proposed to explore the effects of system quality, service quality, information quality, perceived ease of use and perceived usefulness on instructors satisfaction and how their satisfaction will influence their intention to reuse Google Classroom in the future. In the qualitative section, to gain more understanding, instructors were asked to identify the challenges that inhibit the adoption of e-Learning technologies in public universities in Iraq and what are their recommendations to rectify them. Findings: The findings revealed that service quality had no positive influences on the satisfaction of instructors, while other factors had varying levels of influence, the findings further showed that inadequate internet service and students lack of interest are the biggest challenges instructors faced during their experience with Google Classroom. Research limitations/implications: To improve the generalizability of the results, future studies are recommended to include larger samples, in addition, further studies are also advised to take individual traits such as age and gender into consideration. Originality/value: The outcomes of this study are expected to benefit researchers, policymakers and LMS developers who are interested in factors that affect instructors intention to reuse LMS in higher education institutes in developing countries. 2020, Emerald Publishing Limited.